2018
DOI: 10.1177/0022034518759038
|View full text |Cite
|
Sign up to set email alerts
|

GENIPAC: A Genomic Information Portal for Head and Neck Cancer Cell Systems

Abstract: Head and neck cancer (HNC)-derived cell lines represent fundamental models for studying the biological mechanisms underlying cancer development and precision therapies. However, mining the genomic information of HNC cells from available databases requires knowledge on bioinformatics and computational skill sets. Here, we developed a user-friendly web resource for exploring, visualizing, and analyzing genomics information of commonly used HNC cell lines. We populated the current version of GENIPAC with 44 HNC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To achieve this, we compared the mutational profiles of palbociclib-sensitive and -resistant cell lines as determined by cytostatic assay in Figure 1A . We found that two out of three cell line in the resistant group carried mutations in PIK3CA (H1047L and Q546R in ORL-115 and ORL-150, respectively) 12,18 , while none of the palbociclib-sensitive cell lines had any mutations in this gene ( P < 0.001; Figure 3A ). This observation was validated with a larger data set from Genomics of Drug Sensitivity in Cancer (GDSC) comprising of 789 palbociclib-treated cancer cell lines of all available cancer types in the database.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To achieve this, we compared the mutational profiles of palbociclib-sensitive and -resistant cell lines as determined by cytostatic assay in Figure 1A . We found that two out of three cell line in the resistant group carried mutations in PIK3CA (H1047L and Q546R in ORL-115 and ORL-150, respectively) 12,18 , while none of the palbociclib-sensitive cell lines had any mutations in this gene ( P < 0.001; Figure 3A ). This observation was validated with a larger data set from Genomics of Drug Sensitivity in Cancer (GDSC) comprising of 789 palbociclib-treated cancer cell lines of all available cancer types in the database.…”
Section: Resultsmentioning
confidence: 97%
“…Understanding the molecular changes that could influence therapeutic response is vital for identifying subgroups that are most likely to benefit from palbociclib treatment. We leveraged on genomic information on well-characterized cell lines 12,18,24 and showed that PIK3CA mutations are associated with the resistance of OSCC cell lines to palbociclib. Using CAL27 isogenic cell lines, we confirmed that mutations in PIK3CA indeed confer resistance to palbociclib and other clinically approved CDK4/6 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…For metabolic alterations observed in HNSCC a variety of medium and small-scale data sets have been generated as summarised by Shin et al 104 . Furthermore, a genomic information portal for HNSCC cell systems has been set up, detailing clinical and genomic information of 44 cell lines 105 .…”
Section: The Genetic Landscape In Hnscc and Its Clinical Implicationsmentioning
confidence: 99%
“…Different squamous cell carcinoma cell lines exhibited cell type dependent differential expression of TFAP2A and Vimentin (VIM) genes that corroborates inter cell line heterogeneity. The available HNC data bases provide clinical and genomic information on HNC cell systems (102)(103)(104). A holistic HNdb database curates all major omics data and literature on HNC-related genes (105).…”
Section: Transcriptomics Of Hncmentioning
confidence: 99%